Evaluation of four gutta-percha removal techniques for endodontic retreatment - Janaína Barros Alves Medeiros; Marilisa Carneiro Leão Gabardo; Sergio Herrero Moraes; Maria Isabel Anastácio Faria (Revista Sul-Brasileira de Odontologia, 2015)
The endodontic retreatment is the first choice in cases of endodontic treatment failure. Objective: To evaluate the ability of removing gutta-percha from root canal walls, through analyzing the time and different techniques. Material and methods: Sixty extracted human mandibular pre-molars were used. After instrumentation with crown-down technique, the obturation was performed by Tagger’s hybrid technique. The specimens were divided into 4 groups (n = 15), according to removal procedure: group I (manual + solvent), group II (manual + Gates-Glidden + solvent), group III (Protaper Universal Retreatment System) and group IV (Protaper Universal System + solvent). The time period for gutta-percha removal was measured with a stopwatch. The roots were sectioned and the remnants were visually evaluated, according to the following scores: 0 – without remnant, 1 – presence of only cement, 2 – presence of cement and gutta-percha in small amounts, and 3 – presence of cement and gutta-percha in large amounts. Data were statistically evaluated with the GraphPad InStat software. Results: Group II exhibited the shortest time of execution, with significant differences in relation to groups I and IV, which obtained the longest time periods. Group III showed an intermediate time period, with statistically significant differences in relation to group IV. Group IV obtained the best scores of cleaning, although there was no statistical difference among groups. Conclusion: There was no statistical significant difference among the techniques regarding the time and effectiveness in removing filling material from the root canal walls.